HASIL BELAJAR BIOLOGI RANAH KOGNITIF DITINJAU DARI MODEL EVERY ONE IS A TEACHER HERE DAN MINAT BELAJAR SISWA KELAS XI DI SMA NEGERI 1 SUKOHARJO - Pratomo, Eko Nur; Rosyidi, Alvi; Karyanto, Puguh (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? The purposes of this research were to know: 1) the influence of Everyone is a Teacher Here to the mastery of biology result 2) the influence of student?s learning interest to the mastery of biology result; 3) the interaction between learning model and learning interest to the mastery of biology result ; and 4) the influence of better learning model to the mastery of biology result This research was quasi experiment research using Randomized Control Only design. Learning model and learning interest were independent variables and mastery of biology concept was the dependent variable. The population of this research was all of X grade of SMA Negeri 1 Sukoharjo. The samples of this research were the students of class XI IPA 2 as the control class and students of class XI IPA 6 as the experimental class. The sample of this research was established by cluster random sampling. The data about the result of study biology collected by use test and observation. Learning interest meansured by using questionnaires. The analisis of this research was anava two away in different cell and the advance test used Bonfferoni test. . The conclusion of this research were: 1) Problem Based Instruction had significant influence to the mastery of biology result kognitif domain on XI IPA grade of SMA Negeri 1 Sukoharjo; 2) Learning interest hadn?t significant influence to the mastery of biology result kognitif domain on XI IPA grade of SMA Negeri 1 Sukoharjo; and 3) There wasn?t interaction between learning model and learning interest to the mastery of biology result kognitif domain on XI IPA grade of SMA Negeri 1 Sukoharjo Keywords : the mastery of biology resultt, Everyone is a Teacher Here and learning interest